Masterclass: Are You Getting the Most Out of Your Triple Hop Testing? - Sharp, Anthony P; Neville, Jonathon; Cronin, John B (Elsevier BV, 2025)
The triple hop test is a widely used, practical tool that allows physical therapists to assess an athlete's readiness to return-to-sport (RTS) following injury. However, recent consensus statements have raised concerns that hop distance alone may be insufficient to capture the complexity of functional recovery or to fully assess inter-limb symmetry, potentially masking readiness and increasing the risk of reinjury. In this Masterclass: exemplar kinetic and kinematic data for the triple hop are detailed; the utility of the quintuple hop introduced; the distinction between outcome and movement strategy variables discussed within an asymmetry context; and, the integration of accessible, cost-effective technologies within a tier-based framework for RTS assessment outlined. The aim of the article is to enhance the evaluation of movement strategies and support clinicians in making more informed and confident RTS decisions.
Keywords: 4201 Allied Health and Rehabilitation Science; 42 Health Sciences; 4207 Sports Science and Exercise; 1103 Clinical Sciences; 1106 Human Movement and Sports Sciences; Sport Sciences; 4201 Allied health and rehabilitation science; 4207 Sports science and exercise